The Microcomputer and Management of the Time Bound Educational Program - Mosow, David K.; Hewitt, Thomas W. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
An example of the application of microcomputers to education, described in this paper, indicates the possibilities for their widespread use. Forecasters claim that microcomputers will be acquired by more and more individuals and families in the 1980s. This implies that schools will also make greater use of microcomputers, in computer-assisted instruction, school management, and training in computer literacy. At present, few teacher education programs are training their students in computer usage. A Teacher Corps project at the University of South Alabama uses microcomputers both to train its students in computers and to help manage the project. As a time-bound program, the project must meet its objectives before its funding ends. Data on staff activities, entered into a microcomputer by staff members, allows the managers to monitor progress toward project objectives, analyze where staff effort is going, and decide which objectives need more staff time. Because of the project, the university and the local school system have broadened or have investigated further their use of microcomputers in both instruction and management. (RW)
ERIC Note: Not available in paper copy due to light print of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Oriented Programs; Elementary Secondary Education; Higher Education; Management Information Systems; Microcomputers; Program Evaluation; Teacher Education; Computer Literacy; Reports, Descriptive; Opinion Papers